The argument style in research article discussions to support research findings in language studies - Safnil Arsyad; Bambang Kaswanti Purwo; Zifirdaus Adnan (Studies in English Language and Education, 2020)
The argument quality in a research article discussion (henceforth RAD) determines the quality of the article as a whole, and therefore this section must be written as convincingly as possible. However, authors in different disciplines such as Language Studies (LS) may address this section in a different argument style. This study is aimed at investigating how Indonesian writers in LS support their findings in their RADs. There were 40 RADs taken from four different Indonesian journals in LS; the articles were chosen from the latest volumes of the nationally accredited journals. This study used a genre analysis method in which the major source of data is a collection of texts as a product of language activity. The results show that the majority of Indonesian writers use Style 1 (interpreting the research findings or suggesting what the research findings mean), Style 2 (explaining or elaborating the research findings), Style-3 (stating the possible cause/s of the research findings), and Style 4 (illustrating or exemplifying the research findings) to support their research findings. However, unlike international authors, Indonesian writers do not relate their research findings with those of previous related studies; if they do so, it is to confirm the interpretation or explanation of their research results. The results of this study may help Indonesian authors in LS improve the quality of their RADs especially when writing articles in English to be submitted to an international journal.